Genetic and environmental etiology of stability and changes in self-esteem linked to personality: A Japanese twin study. (15th January 2018) - Shikishima, Chizuru; Hiraishi, Kai; Takahashi, Yusuke; Yamagata, Shinji; Yamaguchi, Susumu; Ando, Juko
Abstract: This study used a behavioral genetic approach to examine the genetic and environmental etiology of stability and changes in self-esteem in relation to personality. Multiple genetic analyses were conducted on a longitudinal dataset of self-esteem and Big Five personality scores among young adult Japanese twins over the course of a decade. There were 1221 individuals for whom data were available on both self-esteem and the Big Five personality test at Time 1 and 365 at Time 2. The mean interval between the two times was 9.95 years. Genetic effects on self-esteem were robust, and the same genes were responsible for the stability of self-esteem in individuals over time. Nearly half of the variance in self-esteem was explained by a new genetic factor arising during the decade, suggesting that genetic innovation of self-esteem occurred in early adult life. The genetic and environmental covariance structure between personality and self-esteem in individuals was constant over a decade, providing evidence that the stability of self-esteem was largely attributable to personality. However, genetics for self-esteem independent of personality still contributed to stability over time, differentiating the concept of self-esteem from personality as a trait in terms of its genetic and environmental etiological levels. Highlights: The same genes were responsible for the stability of self-esteem over time. The stability of self-esteem was largely attributable to personality. Genetics for self-esteem independent of personality also contributed to stability. Genetic innovation of self-esteem occurred across a decade in early adult life.